Marketing Communication on Controversial Products - A case study on the tobacco industry - Hadzalic,Soraja; Åkervall,Anna (2011)
The thesis aims to answer a number of questions, for example how are products with restrictions marketed? The thesis is focusing on tobacco. Some of the topics presented in the thesis are marketing communication, tobacco marketing history, ethic and legal restrictions, and a definition on the term controversial.
Keywords: management; Företagsledning; Management of enterprises; B2; tobacco; controversial; Marketing; communication